Impact of maternal anxiety level on the childhood vaccination coverage. - ÖZKAYA, EMİN; ÖZKAYA, EMİN (My University, 2010)
The mother-s mental state as a risk factor for the children-s vaccination status in developing countries has received little attention. The aim of this study was to determine the association between childhood vaccination coverage and maternal anxiety. A total of 195 consecutive infants and their mothers attending a tertiary teaching hospital, department of pediatric outpatient center between January 2008 and September 2009 were included in the study. One hundred five infants who have incomplete vaccination schedule (according to the National Immunization Schedule) were matched with 90 controls (fully vaccinated) and their mothers self-report measure of anxiety level using the State-Trait Anxiety Inventory (STAI), a psychiatric screening instrument. The chi-square test and the logistic regression were used in the statistical analysis. High maternal anxiety levels determined by STAI was associated with increased risk of incomplete vaccination status in infants (odds ratio 4.35, 95% confidence interval 1.87-8.79).This association remained significant after controlling for sociodemographic factors. High maternal anxiety scores may result in incomplete vaccination status in children younger than 3 years.